3. Is DIBH VMAT in left breast related to lower plan complexity than Free Breathing? A multicenter experience. (December 2018) - Russo, S.; Esposito, M.; Hernandez, V.; Saez, J.; Rossi, F.; Paoletti, L.; Bastiani, P.; Tomatis, S.; Mancosu, P.
Abstract : Purpose: VMAT for left breast treatments allows heart sparing without compromising PTV coverage. High plan complexity could occur if Free Breathing (FB) technique is adopted. Deep Inspiration Breath Hold (DIBH) procedure increases the heart-to-breast distance, allowing heart dose reduction. The aim of the present work was to investigate if the cardiac-sparing benefits of the DIBH technique corresponded to plan modulation and complexity reduction. Methods: Seven left side breast cases were considered by two centers with different treatment planning systems (TPS) (Monaco 5.0 and Eclipse 11) and Linac devices (Elekta Synergy and Varian True Beam). VMAT plans were elaborated in FB and DIBH. Dose prescriptions was 40.5 Gy for the whole breast ( PTV breast ) and 48 Gy for the tumor bed ( PTV boost ) in 15 fractions. PTV breast 98 % > 38.5 Gy, PTV boost 98 % > 45.7 Gy, and maximum dose to PTV boost < 107 % were asked. Specific OARs constraints were: V 18Gy < 5 % and Mean Heart Dose (MHD) < 4 Gy for heart; D mean < 10 Gy and V 20Gy < 10 % for left lung; D mean < 3 Gy for right lung and breast. All plan data were collected in DICOM-RT format. Plan complexity was evaluated by scoring the mean MLC gap (MLCgap), Monitor Units (MU), and a global parameter accounting for plan quality and dosimetric scoring, defined as GP = (MIxMHD/PTVbreast 98%). MI is the modulation index defined by Park et al.[1] . Comparison of FB and DIBH plan parameters was performed using a one-sided Wilcoxon signed ranks test for related samples (p-value < 0.05 was considered significant). Results: Higher mean MLCgap for DIBH plans were scored; MU and GP resulted significant lower in DIBH (see table). DIBH-VMAT plans were associated with a significant reduction in MHD and V HEART 18 Gy (respectively p < 0.003 and p < 0.005; see figure) and a significant better PTV coverage ( PTV breast 98 % DIBH 38.9 ± 0.6 Gy vs FB 37.9 ± 1.4 Gy, p < 0.008). Conclusions: The cardiac-sparing benefits relative to DIBH VMAT left breast technique were achieved with a lower plan complexity than FB treatments.